If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3p + 3) + -2(6 + -14p) = 3(1 + 6p) Reorder the terms: -3(3 + 3p) + -2(6 + -14p) = 3(1 + 6p) (3 * -3 + 3p * -3) + -2(6 + -14p) = 3(1 + 6p) (-9 + -9p) + -2(6 + -14p) = 3(1 + 6p) -9 + -9p + (6 * -2 + -14p * -2) = 3(1 + 6p) -9 + -9p + (-12 + 28p) = 3(1 + 6p) Reorder the terms: -9 + -12 + -9p + 28p = 3(1 + 6p) Combine like terms: -9 + -12 = -21 -21 + -9p + 28p = 3(1 + 6p) Combine like terms: -9p + 28p = 19p -21 + 19p = 3(1 + 6p) -21 + 19p = (1 * 3 + 6p * 3) -21 + 19p = (3 + 18p) Solving -21 + 19p = 3 + 18p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-18p' to each side of the equation. -21 + 19p + -18p = 3 + 18p + -18p Combine like terms: 19p + -18p = 1p -21 + 1p = 3 + 18p + -18p Combine like terms: 18p + -18p = 0 -21 + 1p = 3 + 0 -21 + 1p = 3 Add '21' to each side of the equation. -21 + 21 + 1p = 3 + 21 Combine like terms: -21 + 21 = 0 0 + 1p = 3 + 21 1p = 3 + 21 Combine like terms: 3 + 21 = 24 1p = 24 Divide each side by '1'. p = 24 Simplifying p = 24
| 2x+2=34x | | 2x+0.4=18 | | (3x+6)/12=10 | | -2(x-4)=4(2x-3) | | 6x-3x+5=35 | | X+1/2=2x-1/5 | | x+75=125 | | 3/10b-(1/10b-10) | | 2(f+3)+4f=6+6t | | -(7-4x)= | | x-75=125 | | 2(4x+8)=5(x-7) | | x-175= | | x^2+x^2+14x+49=4x^2+4x+1 | | r(x)=6x | | 2.8(3x-2)=-12.32 | | (-12x+6)+(4x-12)= | | 4+7x=-9x+5 | | [a-b]=[a]-[b] | | -4-4=8 | | (-2x-1)-(x-7)= | | 7x+5=4(3x-5) | | 14=-(p+8) | | 5/6x-1/3=x-3/2 | | [a+b]=[a]+[b] | | 1v-2=78-16v-12 | | 14=(p+8) | | 7/8-1x=13/8 | | 1/7f-51/2=9/14 | | 0=8x+2 | | 1v-2=78-16v+12 | | 3(2c-2)-2c=o |